Modelling lactation curve in dairy sheep rose under extensive production system - Cadavez, Vasco (2008)
The objective of this study was to compare the goodness-of- fit of four mathematical functions (Wilmink, 1987; Ali and Schaeffer, 1987; Guo and Swalve, 1995; and a cubic regression model) for modeling lactation curve on dairy ewes. Data comprising 53,428 test-day records of daily milk yield (DMY) of 11,251 ewes raised under extensive production system, collected during six consecutive years (2000 to 2005) by the milking recording program of the Churra da Terra Quente (CTQ) dairy sheep breed, were used. Test-day records registered before 30 and after 150 days in milk (DIM) were discharged. All models presented similar fitting quality, with coefficient of determination between 71.0 and 71.3%, and underestimate the DMY for high production levels; this trend was more pronounced for Wilmink model. All models presented similar data fitting-quality, and Wilmink model presented higher difficulties in modeling the beginning and the end of lactation curve, however, being a model with less parameters can present advantages in dairy ewes productions systems where small number of test days controls per ewe can occur.